Obstructive Sleep Apnea and Circulating Potassium Channel Levels. Issue 8 (19th August 2016) - Jiang, Ning; Zhou, Anyu; Prasad, Bharati; Zhou, Li; Doumit, Jimmy; Shi, Guangbin; Imran, Hafiz; Kaseer, Bahaa; Millman, Richard; Dudley, Samuel C.
Abstract : Background: Cardiac arrhythmias and sudden cardiac death are more frequent in patients with obstructive sleep apnea (OSA). OSA is associated with QT prolongation, and QT prolongation is an independent risk factor for sudden cardiac death. Because QT prolongation can be mediated by potassium channel loss of function, we tested whether OSA or continuous positive airway pressure therapy altered mRNA expression of circulating white blood cell potassium channels. Methods and Results: In total, 28 patients with OSA newly diagnosed by polysomnogram and 6 participants without OSA were enrolled. Potassium channel levels in white blood cells at baseline and at a 4‐week follow‐up visit were compared. There was a significant inverse correlation between the severity of the OSA stratified by apnea–hypopnea index and mRNA expression of the main potassium channels assessed: KCNQ1 ( r =−0.486, P =0.007), KCNH2 ( r =−0.437, P =0.016), KCNE1 ( r =−0.567, P =0.001), KCNJ2 ( r =−0.442, P =0.015), and KCNA5 ( r =−0.468, P =0.009). In addition, KCNQ1, KCNH2, and KCNE1 inversely correlated with the oxygen desaturation index 4. After 4 weeks of continuous positive airway pressure therapy, circulating KCNQ1 and KCNJ2 were increased 1.4±0.4‐fold ( P =0.040) and 2.1±1.4‐fold ( P =0.046) in the moderate OSA group. Compared with patients with mild or moderate OSA, patients with severe OSA had a persistently higher apnea–hypopnea index (mild 2.0±1.8, moderate 1.0±0.9, severe 5.8±5.6; P =0.015), perhaps explaining why the potassium channel changes were not seen in the severe OSA group. Conclusions: The mRNA expression of most potassium channels inversely correlates with the severity of OSA and hypoxemia. Continuous positive airway pressure therapy improves circulating KCNQ1 and KCNJ2 in patients with moderate OSA.